Візуальні методи контролю якості виготовлення металевих деталей за допомогою технічного зору - Селіванов, С. І.; Стрілкова, Т. О. (ХНУРЕ, 2025)
This study focuses on improving automated quality control of metal parts using machine vision. The correlation image processing method enables accurate detection of defects such as dents, burrs, cracks, and scratches. The research includes modeling defect illumination using high-resolution cameras and image enhancement techniques. Future studies will expand defect detection capabilities and integrate with production management systems.
Keywords: технічний зір; візуальні методи контролю якості